การชักนำให้เกิดมิวเตชันด้วยแสงอัลตราไวโอเลตในเห็ดหลินจือ Ganoderma lucidum ที่สามารถย่อยสลายลิกนิน - นภา จิรมิตตานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The single cells of Ganoderma lucidum, MUG001 and MUGS, from the cutting cell under Microscrope were induced for mutation with ultraviolet light. These single cells were screened for ketoconazole resistant, ability to produce colored precipitate on guaiacol-containing agar plates and the highest level of manganese peroxidase activity and laccase activity. From 70 colonies, there were one hyperligninolytic mutant, MUG001-50S-2, could produce the highest level of manganese peroxidase activity and laccase activity. The highest manganese peroxidase activity was 0.00017U/ml when cultivated in liquid medium containing eucalyptus paper pulp at pH 3, 25 ํC and 7 days incubate. The highest laccase activity was 0.0015U/ml at pH 5, 30 ํC and 11 days incubate. When it was compare with wild type, MUG001, it was found that manganese peroxidase activity and laccase activity of MUG001-50S-2 were increasing to 5 and 2.73 folds respectively. Biobleaching of hardwood kraft pulp by crude enzyme from this mutant strain (12.5IU/gOD) was investigated and compared with unbleach hardwood kraft pulp. It was found that pulp brightness increased from 48.6% to 51.9% ISO brightness, kappa number decreased from 11.17 to 6.8, and burst index increase from 0.704 kPa.m[superscript 2]/g to 1.052 kPa.m[superscript 2]/g significantly.